Symbolically Annihilating Female Police Officer Capabilities: Cultivating Gendered Police Use of Force Expectations? - Wilson, Franklin T. (Women & criminal justice, 2020)
This first step cultivation analysis examines the quantity, temporal dynamics, and stance of municipal police officer use of force depictions based on the gender of the officer. The 112 theatrically released films that comprise the core cop film genre were systematically identified. Subsequently, a population of 468 police use of force scenes was identified to serve as the units of analysis for this study. Findings revealed male officer use of force scenes appeared across all 40 years of films. Female officer use of force scenes, however, were highly restricted to specific films, years, and often dwarfed by male scenes within films. Lone female officer use of force scenes saw their highest representation in the 1980s but declined in the 1990s and 2000s, becoming increasingly dependent on a male officer’s presence. Implications of such patterns are discussed as well as potential second step cultivation studies.